2021
DOI: 10.1021/acs.jctc.0c00638
|View full text |Cite
|
Sign up to set email alerts
|

Coarse-Grained Force Fields from the Perspective of Statistical Mechanics: Better Understanding of the Origins of a MARTINI Hangover

Abstract: The popular MARTINI coarse-grained model is used as a test case to analyze the adherence of top-down coarse-grained molecular dynamics models (i.e., models primarily parametrized to match experimental results) to the known features of statistical mechanics for the underlying all-atom representations. Specifically, the temperature dependence of various pair distribution functions, and hence their underlying potentials of mean force via the reversible work theorem, are compared between MARTINI 2.0, Dry MARTINI, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 49 publications
1
74
0
Order By: Relevance
“…Despite the numerous improvements and even wider applications opened up by Martini 3, limitations of this coarse‐graining approach must be kept in mind. Certain limitations apply generally to the Martini force field, [ 8,24,75 ] and include a nonquantitative agreement with experimental free energies of solvation and narrower fluid ranges due to the use of the 12‐6 Lennard‐Jones potential, and an entropy–enthalpy imbalance—due to enthalpy compensating for the loss of degrees of freedom upon coarse‐graining—which is known to affect the temperature dependence of several properties, [ 10,24 ] Other limitations pertain more specifically to the systems subject of the present study, namely small‐molecules containing ring‐like structures described by finer mappings. As shown in Section 3.4, conformations driven by quadrupolar interactions, such as T‐shaped stacking, are not captured by standard Martini models due to the lack of specific electrostatic interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the numerous improvements and even wider applications opened up by Martini 3, limitations of this coarse‐graining approach must be kept in mind. Certain limitations apply generally to the Martini force field, [ 8,24,75 ] and include a nonquantitative agreement with experimental free energies of solvation and narrower fluid ranges due to the use of the 12‐6 Lennard‐Jones potential, and an entropy–enthalpy imbalance—due to enthalpy compensating for the loss of degrees of freedom upon coarse‐graining—which is known to affect the temperature dependence of several properties, [ 10,24 ] Other limitations pertain more specifically to the systems subject of the present study, namely small‐molecules containing ring‐like structures described by finer mappings. As shown in Section 3.4, conformations driven by quadrupolar interactions, such as T‐shaped stacking, are not captured by standard Martini models due to the lack of specific electrostatic interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Coarse-grained simulations have also been successfully used in the study of nanoparticles partitioning into lipid bilayers, e.g., [652,653] or where large-scale screening is performed for hundreds of drugs [654][655][656][657][658]. It should be noted that the MARTINI model was recently reparametrized (MARTINI 3) [659] to fix problems related to the imbalance of interactions between beads of various sizes leading to unrealistically strong interactions, e.g., proteinprotein interactions [660][661][662].…”
Section: Translocation Through the Membranementioning
confidence: 99%
“…The density profiles of the phosphate groups show a large variability both in height and in width (top right in Figure 2 ). This can be likely imputed to differences in the CG beads, and in the bead–bead interactions, used in the different CG FFs, slightly different approximations in the enthalpy/entropy balance in the models (that unavoidably accompany the various CG schemes 58 ) can, for example, make the thermal vibrations larger/smaller, broadening/narrowing the density distributions. A great variability is present in membrane compressibility (bottom left in Figure 2 ), irrespective of the FF resolution.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was shown that Martini 2.2 and Dry Martini CG FFs, respectively, tend, on average, to overstructure and understructure the bilayers compared to AA FFs. 58 However, all these analyses and comparisons provide evidence that is limited to the average characterization of the bilayers, while, on the other hand, it has been shown that the behavior of complex supramolecular assemblies (such as also lipid bilayers) may be strongly controlled by local events, or fluctuations, that cannot be captured with average evaluations. 39,40,61 To move our investigation to a deeper level, similarly to a recent study 37 where typical ice nucleation sites were probed in a QM-based liquid water model by means of a SOAP analysis, we investigated the transition of a lipid bilayer between the liquid phase and the gel phase.…”
Section: ■ Results and Discussionmentioning
confidence: 99%